Foliar Spraying Alphatocopherol Enhances Salinity Stress Tolerance in Wheat Plant Triticum Aestivum L. - AL-Kazzaz, Amel Ghanim Muhmood; AL-Kareemawi, Inas Hasseb Khamees (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Alphatocopherol is a vitamin and antioxidant compound that plays a crucial role in amelioration of biotic and abiotic stresses and protects plants from stress â€“ induced cellular  oxidation .The experiment was carried out in a green garden of the Department of  Biology, College of Education for Pure Sciences Ibn-AL-Haitham ,University of Baghdad during 2018 â€“ 2019 to evaluate the potential effects of foliar application with (0 ,50 ,100 ,150 ,200 mg.L-1) alphatocopherol on growth, yield components and the activity of antioxidant system of wheat plant under sodium chloride stress(0 ,75 , 150 ,225mM.L-1) .Results indicated that sodium chloride caused reduction in shoot dry weight and some yield components (biological yield , no. spikelet .spike-1 and 1000 grain weight)and a significant increase in the endogenous proline acid and alphatocopherol concentration and raised catalase activity. Foliar spray of alphatocopherol improved salt stress tolerance in wheat plant by increasing all the parameters.